ANALISIS KUALITAS KOMUNIKASI INTERPERSONAL DAN INTEAKSI REMAJA PECANDU GAME ONLINE MLBB DENGAN KELUARGA DI KELURAHAN MAREKU - Muhammad Arfan Said; Nur Akbar A. Koja; M. Jufri Sukandi (JOEL: Journal of Educational and Language Research, 2023)
The development of technology and networks at this time triggers the emergence of various things that can be carried out depending on the internet network, one of which is online games. Online games are now a hobby for teenagers and children so that they can reduce other activities. One online game that is now a favorite of some people, especially teenagers, is MLBB. Frequently playing MLBB online games for such a long duration in a day, causing changes in interpersonal communication and interaction with family. The purpose of this study was to determine the quality of interpersonal communication and interaction among young online game addicts and the factors that influence the quality of interpersonal communication and interaction between online game addict adolescents and their families in Mareku Village. The method used in this research is qualitative research with a phenomenological approach. By using six key informants, MLBB online game addicts and 6 supporting informants. In this study, it can be concluded that interpersonal communication and interactions between online game addicts and their families are less effective. This is due to the habit of playing online games with a very high duration of time, which causes changes in interpersonal communication and interaction within the family environment and factors that influence the quality of interpersonal communication and interactions of adolescent online game addicts with their families who tend to be more open, empathetic, and positive. sympathy and influence that goes with every family member